Prisões sem guardas: uma experiência liderada por grupos religiosos - Victor Neiva e Oliveira (2013)
The organizational dynamics of prisons are usually characterized by the presence of guards, who, with criminal directors, takes care for the safety, discipline and internal order. However, in recent decades, we witness the advent of prisons administered in independently way by christian groups from civil society in cooperation with the prisoners themselves. This experience is known as APAC, because it was created by the nonprofit organization Associação de Proteção e Assistência aos Condenados APAC. Instead of criminal directors, the members of NPO are responsible for the central control of the prison, and, on the other hand, the prisoners themselves occupy the place once reserved to the guards, which involves tasks related to the vigilance, discipline and security services. This work, based on a field research conducted in two prisons administered by APAC in the state of Minas Gerais, analyzes the dynamics of the relationship between the prisoners and between these and the christian staff in these establishments. By unveiling intricacies of the apaqueana prisons way of life, we intend to show how it is possible perform an experience with this nature.